ASSISTÊNCIA ESTUDANTIL NA EDUCAÇÃO SUPERIOR: A PERMANÊNCIA DE ESTUDANTES MIGRANTES DA UFMS - Carolina Maria Paixao Araujo (2021)
The dissertation seeks to analyze the effectiveness of Student Assistance in serving migrant students at the Federal University of Mato Grosso do Sul (UFMS), at the Nova Andradina Campus (CPNA), after the implementation of the National Student Assistance Program (PNAES), by Decree nº 7,234 in 2010, until the year 2019. It was analyzed, through qualitative research, based on official documents, scientific productions and quantitative data, such as the Federal University of Mato Grosso do Sul, specifically the Nova Andradina Campus, it operationalizes Student Assistance as an instrument that facilitates the permanence of migrant students in undergraduate courses, considering the specificities of these individuals lacking a family network for economic, cultural and emotional support in the current cities where they live. The theoretical framework consisted of the configuration of the State in capitalist society, the context of struggles and contradictions in which social and Student Assistance policies fit, and the specificities of migrant students in higher education. As a quantitative database, a spreadsheet with socioeconomic information of students enrolled at the Nova Andradina Campus in 2019 was used, as well as the number of subscribers and beneficiaries with assistance in the same year, made available by the Dean of Student Affairs at the Federal University of Mato Grosso do Sul. For the theoretical construction, the context of the reduction of social policies as expenditures and not public investments, the neoliberal conjuncture of State and education reform, which views Student Assistance as damage to the State, but which still represents a response to meeting the demands of the working class; and the movement of contradictions, historicity and totality that involve the management and operationalization of Student Assistance in different governments and State models. With this, the research presents the profile of migrant students and intends to contribute to the discussion on the role of the government in proposing policies for low-income students, since they are affected by the social issue and rely on student assistance as a way to minimize the situations of social inequalities resulting from their working class condition and specificities, as young migrants, in order to remain in higher education.